"Why Am I the Way I Am?" Narrative Work in the Context of Stigmatized Identities. (December 2017) - Rance, Jake; Gray, Rebecca; Hopwood, Max
There are particular complexities faced by people attempting to tell their stories in the context of social stigma, such as the hostility which often surrounds injecting drug use. In this article, we identify some of the distinct advantages of taking a narrative approach to understanding these complexities by exploring a single case study, across two life-history interviews, with "Jimmy, " a young man with a history of social disadvantage, incarceration, and heroin dependence. Drawing on Miranda Fricker's notion of "hermeneutical injustice, " we consider the effects of stigmatization on the sociocultural practice of storytelling. We note the way Jimmy appears both constrained and released by his story—how he conforms to but also resists the master narrative of the "drug user." Narrative analysis, we conclude, honors the complex challenges of the accounting work evident in interviews such as Jimmy's, providing a valuable counterpoint to other forms of qualitative inquiry in the addictions field.